Simultaneous Tenfold Brightness Enhancement and Emitted‐Light Spectral Tunability in Transparent Ambipolar Organic Light‐Emitting Transistor by Integration of High‐k Photonic Crystal. (25th April 2017) - Natali, Marco; Quiroga, Santiago D.; Passoni, Luca; Criante, Luigino; Benvenuti, Emilia; Bolognini, Gabriele; Favaretto, Laura; Melucci, Manuela; Muccini, Michele; Scotognella, Francesco; Di Fonzo, Fabio; Toffanin, Stefano
Abstract : In organic light‐emitting transistors, the structural properties such as the in‐plane geometry and the lateral charge injection are the key elements that enable the monolithic integration of multiple electronic, optoelectronic, and photonic functions within the same device. Here, the realization of highly integrated multifunctional optoelectronic organic device is reported by introducing a high‐capacitance photonic crystal as a gate dielectric into a transparent single‐layer ambipolar organic light‐emitting transistor (OLET). By engineering the photonic crystal multistack and bandgap, it is showed that the integration of the photonic structure has a twofold effect on the optoelectronic performance of the device, i.e., i) to modulate the spectral profile and outcoupling of the emitted light and ii) to enhance the transistor source–drain current by a 25‐fold factor. Consequently, the photonic‐crystal‐integrated OLET shows an order of magnitude higher emitted power and brightness with respect to the corresponding polymer‐dielectric device, while presenting as‐designed electroluminescence spectral and spatial distribution. The results validate the efficacy of the proposed approach that is expected to unravel the technological potential for the realization of highly integrated optoelectronic smart systems based on organic light‐emitting transistors. Abstract : Monolithic integration of a high‐ k 1D photonic crystal as the gate dielectric in a transparent organic light‐emitting transistor is reported. One order of magnitude enhancement of the emitted power in ambipolar conditions and as‐predicted tunability in the spectral profile of the emitted light.